Analysis Of Slope Stability Using Bamboo As An Alternative Slope Reinforcement (Case Study In Kaliwungu – Boja Street, Darupono Village, Kendal District) - Mohammad Abdul Wahhab; Mokhamad Rizki Ramadhan (International Conference on Coastal and Delta Areas, 2017)
Bamboo is a plant that can be found in Indonesia, however the utilization of bamboo as a structure material is rarely to use in our society. This study was conducted with the objective to analyze the performance of bamboo with respect to soil stability. Bamboo was used as an alternative soil reinforcement to landslide in Kaliwungu – Boja street, Darupono village, Kendal District. Two kinds of bamboos analyzed here were Betung and Tali bamboos having diameter 20 centimeters and 15 centimeters respectively. The index and engineering properties of a soil from Boja street were tested. To analyze the safety factor of the slope of Boja street, Plaxis v.8 and Slope/W were used. The result showed that 1) from soil test the cohesion (c) is 50,995 kN/m2, phi (φ) is 36o, γsat is 16,374 kN/m3, and γunsat is 12,534 kN/m3. 2) the safety factor of the slope in natural condition using Plaxis v.8 and Geostudio (slope/w) is 1,32 and the safety factor with traffic loads is 1,26 – 1,29, with these safety factor, the slope will slide because the safety factor is <1,5. Therefor, the slope strengthened with bamboo, so the safety factor of the slope increased to 1,77 - 1,87. Keywords: Betung Bamboo, Tali Bamboo, Slope, soil reinforcement, Plaxis, Geostudio